Extramedullary disease relapse and progression after blinatumomab therapy for treatment of acute lymphoblastic leukemia. Issue 3 (11th October 2021) - Aldoss, Ibrahim; Otoukesh, Salman; Zhang, Jianying; Mokhtari, Sally; Ngo, Dat; Mojtahedzadeh, Mona; Al Malki, Monzr M.; Salhotra, Amandeep; Ali, Haris; Aribi, Ahmed; Sandhu, Karamjeet S.; Arslan, Shukaib; et al.
Abstract : Background: Blinatumomab has demonstrated encouraging activity in relapsed/refractory (r/r) and minimal residual disease–positive (MRD+) acute lymphoblastic leukemia (ALL). Extramedullary disease (EMD) relapse or relapse with CD19– disease has been observed after blinatumomab therapy in patients with r/r or MRD+ ALL. However, the pathophysiology and risk factors of treatment failure are not fully understood. Methods: This study retrospectively reviewed the outcomes of adult patients with B‐cell ALL treated with blinatumomab (n = 132) for either r/r (n = 103) or MRD+ disease (n = 29) at the authors' center (2013‐2021) and analyzed factors associated with treatment response and EMD failure. Results: The overall response rate was 64%. A lower marrow blast burden before blinatumomab ( P = .049) and no history of previous EMD ( P = .019) were significantly associated with a higher response. Among the patients who responded to blinatumomab, 56% underwent consolidation with allogeneic transplantation. Blinatumomab failure was observed in 89 patients; 43% of these patients (n = 38) either progressed or relapsed at extramedullary sites. A history of extramedullary involvement (53% vs 24%; P = .005) and retention of CD19 expression at the time of relapse/progression (97% vs 74%; P = .012) were associated with a higher risk for extramedullary failure. Central nervous system (CNS) failure after blinatumomab was encountered in 39% of the patients with EMD. Conclusions: A history of EMD predicted an inferior response to blinatumomab therapy with a higher risk for relapse/progression at extramedullary sites (particularly CNS). Consolidation with allogenic transplantation in patients who primarily responded to blinatumomab did not abrogate the risk of extramedullary relapse. The incorporation of extramedullary assessment and the intensification of CNS prophylaxis may help in addressing extramedullary failure. Lay Summary: Extramedullary failure is common during blinatumomab therapy for relapsed/refractory acute lymphoblastic leukemia. A history of extramedullary disease predicts an inferior response to blinatumomab therapy and a higher risk for relapse/progression at extramedullary sites. Most extramedullary failure cases retain CD19 expression. Abstract : Extramedullary failure is common during blinatumomab therapy for relapsed/refractory acute lymphoblastic leukemia. A history of extramedullary disease predicts an inferior response to blinatumomab therapy and a higher risk for relapse/progression at extramedullary sites.